2013
DOI: 10.1080/17458080.2011.557841
|View full text |Cite
|
Sign up to set email alerts
|

Functionalised gold nanoparticles for selective induction ofin vitroapoptosis among human cancer cell lines

Abstract: The interaction of citrate-and polyethylene imine (PEI)-functionalised gold nanoparticles (GNP) with cancer cell lines with respect to the cellular response was studied. It was found that GNP/citrate nanoparticles were able to induce apoptosis in human carcinoma lung cell lines A549, but GNP/PEI did not show any reduction in the viability of the cells in human breast cancer cell line MCF-7 and A549 cell lines. FACS data confirmed that the number of apoptotic cells increased with increase in the concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 23 publications
7
26
0
Order By: Relevance
“…The peaks at 1636 cm −1 and 3254 cm −1 can be assigned to the O-H scissor bonds and O-H stretching bonds, respectively. These data confirm that citrate served as a capping agent in Au-NPs [41].…”
Section: Physical Properties Of Au-npssupporting
confidence: 77%
“…The peaks at 1636 cm −1 and 3254 cm −1 can be assigned to the O-H scissor bonds and O-H stretching bonds, respectively. These data confirm that citrate served as a capping agent in Au-NPs [41].…”
Section: Physical Properties Of Au-npssupporting
confidence: 77%
“…Once further modified with PSS and PDDAC, the cytotoxity of Au NPs was significantly reduced [79]. Another study also showed that citrate-coated Au NPs induce apoptosis in human lung cancer A549 cells, but Au NPs coated with polyethylenimine (PEI) showed negligible toxicity to both A549 cells and MCF-7 cells [107]. Another study showed that the cytotoxicity of triphenylphosphine monosulfonate-modified Au NPs of 1.4 nm (Au1.4MS) and glutathione-modified NPs of 1.1 nm (Au1.1GSH) was different.…”
Section: Interaction Of Au Nps With Cellsmentioning
confidence: 99%
“…The peak values corresponding to the C-O stretching shifted from 1055 to 1061 cm -1 due to presented citrate salts. The symmetric and anti-symmetric stretching of COOat 1395 and 1576 cm -1 at FTIR spectra of MC8SC3 hydrogel sample was also support the interaction of citrate ions and MC (9). SEM micrographs reveal the interconnected porous microstructure.…”
Section: Discussionmentioning
confidence: 52%
“…Functional groups of the synthesized hydrogels were detected by using FTIR spectrometer from 4000 to 400 cm-1 with Thermo Scientific Smart Orbit model (9). The morphology and microstructure of the lyophilized hydrogels were examined by using scanning electron microscopy (SEM) (Zeiss, Evo LS10) with 10kV accelerating voltage at Yıldız Technical University, Istanbul, Turkey (30).…”
Section: Methodsmentioning
confidence: 99%